2016
DOI: 10.1007/s13277-016-5012-3
|View full text |Cite
|
Sign up to set email alerts
|

PCA3 long noncoding RNA modulates the expression of key cancer-related genes in LNCaP prostate cancer cells

Abstract: Prostate cancer antigen 3 (PCA3) is a prostate-specific long noncoding RNA (lncRNA) involved in the control of prostate cancer (PCa) cell survival, through modulating androgen receptor (AR) signaling. To further comprehend the mechanisms by which PCA3 modulates LNCaP cell survival, we characterized the expression patterns of several cancer-related genes, including those involved in epithelial-mesenchymal transition (EMT) and AR cofactors in response to PCA3 silencing. We also aimed to develop a strategy to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 38 publications
2
57
1
1
Order By: Relevance
“…Rather, it is involved in several mechanisms, including regulation of cancer genes and AR cofactors as well as partial modulation of EMT [48]. …”
Section: Long Non-coding Rnas and Prostate Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Rather, it is involved in several mechanisms, including regulation of cancer genes and AR cofactors as well as partial modulation of EMT [48]. …”
Section: Long Non-coding Rnas and Prostate Cancermentioning
confidence: 99%
“…The experimental knockdown of PCA3 leads to upregulation of epithelial markers E-cadherin, claudin-3, and cytokeratin-18, with consecutive downregulation of the mesenchymal marker vimentin [48]. Of note however, is that the EMT pattern is not completely reversed by PCA3 knockdown; mesenchymal markers zinc finger protein SNAI1 (Snail), Twist-related protein 1 (TWIST1) and Slug are still found upregulated and epithelial markers cytokeratin-8 and claudin-4 downregulated upon PCA3 knockdown [48].…”
Section: Long Non-coding Rnas and Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many reports have shown that lncRNAs play an oncogenic or tumor suppressive role in various cancers, such as breast, gastric, colorectal cancers and hepatocellular carcinoma [1719]. Emerging evidences have demonstrated that dysregulation of lncRNAs has been implicated in multiple cellular biological processes, such as cell proliferation, apoptosis, cancer metastasis, as well as tumorigenesis [20, 21]. Furthermore, several lncRNAs were reported to be involved in OS progression and tumorigenesis [22].…”
Section: Introductionmentioning
confidence: 99%